Political participation of youth: perception analysis: Youth Politics and Perception Analysis (Journal of the Sylhet Agricultural University, 2026)
Youth is the epitome of a creative force. As a dynamic source of innovation, they have participated, contributed, and even catalyzed essential changes in political systems, power-sharing dynamics and history. Youths have reshaped the democratic trajectory ofBangladesh from 1952 to the July 2024 revolution, demonstrating an indomitable spirit of sacrifice. But unfortunately, a significant portion of the youth are detached from the political process. As voting is widely considered the most important form of politicalparticipation, this study was carried out to analyze the perception of youths about the electoral process in Bangladesh and identify the factors that trigger their disengagement. The study was conducted in Sylhet City Corporation among 471 participants from diversebackgrounds. A convergent parallel mixed-methods study design was used in this study to collect, analyse and interpret quantitative and qualitative data. A semi-structured questionnaire was used to collect data, which were analysed using SPSS and content analysis. The results show that 50.3% of respondents consider the existing electoral process flawed, and 58.8% believe that the existing electoral process does not reflect the demands of the youth. The study suggests that to ensure youth engagement, the administration andthe election commission must play a neutral role. Moreover, credible candidates must be nominated, and a peaceful environment should be ensured at the polling centers to motivate youths to participate in the electoral process.J. Sylhet Agril. Univ. 12(2): 67-76, 2025